Polarization Stable Triband Thin Square-Shaped Metamaterial Absorber - M. L. S. N. S. Lakshmi; S. Prasad Jones Christydass; S. Kannadhasan; K. Anguraj; Jyotir Moy Chatterjee (International Journal of Antennas and Propagation)
An efficient triband metamaterial absorber is presented for X- and K-band applications. The unit cell is of simple shape. The absorber is fabricated on a thin polyamide, which makes it flexible. The parameters of the designed absorber are optimized. The simulated results show that it has good absorption rate and polarization stability. The stability is exhibited over a wide range in both TE and TE modes of the incident waves. The measured results are on par with the simulated results. The measurement is carried out with the waveguide measurement method.